2019
DOI: 10.1111/ruso.12295
|View full text |Cite
|
Sign up to set email alerts
|

Rurality and Income Inequality in the United States, 1975–2015

Abstract: Recent events have focused attention on the perceived widening of the economic divide between urban and rural areas, and on the continued rise of national income inequality. We demonstrate that, in fact, the average income gap between urban (metropolitan) and rural (nonmetropolitan) households has not risen over the past 40 years, and makes virtually no contribution to national income inequality. Rising national inequality is driven by rising inequality within both urban and rural America, not by an urban/rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In addition to these rural-urban differentials in population composition and social structure, rurality (and urbanicity) may be associated with income inequality on their own terms. Prior work has suggested that sub-national income inequality may vary systematically between rural and urban areas (e.g., Hertz & Silva 2019;McLaughlin 2002;Moller et al 2009, Nord 1980. For example, Van Heuvelen (2018) draws on the work on Simon Kuznets and other contemporary scholars to suggest that urban areas should be characterized by higher levels of inequality than rural places, since the former are most likely to be characterized by dynamic economies, highlyeducated workers, and other characteristics associated with the attainment of high pay that skews the income distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these rural-urban differentials in population composition and social structure, rurality (and urbanicity) may be associated with income inequality on their own terms. Prior work has suggested that sub-national income inequality may vary systematically between rural and urban areas (e.g., Hertz & Silva 2019;McLaughlin 2002;Moller et al 2009, Nord 1980. For example, Van Heuvelen (2018) draws on the work on Simon Kuznets and other contemporary scholars to suggest that urban areas should be characterized by higher levels of inequality than rural places, since the former are most likely to be characterized by dynamic economies, highlyeducated workers, and other characteristics associated with the attainment of high pay that skews the income distribution.…”
Section: Introductionmentioning
confidence: 99%
“…First, we fill a gap in evidence about changing rural‐urban differentials in income inequality during a period of growing macro‐level inequalities. Prior work has either not focused explicitly on rural‐urban comparisons, produced estimates for only some of the 1970–2016 time period we study here, or focused on alternative geographic scales (e.g., Hertz and Silva 2020; McLaughlin 2002; Peters 2013). Our study, therefore, represents the only known county‐level analysis to track absolute levels of income inequality across the rural‐urban continuum since 1970, when the declining income disparities of the mid‐twentieth century began to reverse.…”
Section: Introductionmentioning
confidence: 99%
“…Less commonly examined, however, is the generating processes underlying these trends and how they differ by gender. This paper extends earlier research (Hertz and Silva 2019) on the role of auxiliary income sources in the development of household income inequality to focus solely on the growth of earnings inequality per se.…”
Section: Introductionmentioning
confidence: 70%
“…This lack of research is surprising because the Black Belt is historically (in)famous for segregation and integration issues. The region continues to face racial isolation and economic hardship, reflecting patterns across the United States in which rural minorities are among the most economically disadvantaged members of American society (Hertz and Silva 2020;Slack 2014;Slack and Jensen 2002). The Black Belt is no exception.…”
Section: Private Schools and School Segregation In The South And The Black Beltmentioning
confidence: 99%